The World of Castles - Steele, Philip; Edited by Wilson, Clive (London Kingfisher, 2005)
From how murder holes were used, to who did the laundry, find out all there is to know about life in a fortress home. The world of castles opens up as you go to a medieval market, look in on a friendly joust, and experience an enemy siege.
Include Color Illustrations